2021
DOI: 10.1080/14767058.2020.1849121
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic assessment of cesarean section scar to vesicovaginal fold distance: an instrument to estimate pre-labor uterine rupture risk

Abstract: Background: The number of Cesarean sections (CS) is growing worldwide, intensifying the risk of complications in subsequent pregnancies and leading to increased maternal and fetal morbidity and mortality . In particular, the literature shows a higher risk of uterine rupture (UR) in subsequent pregnancy with trial of labor after cesarean section (TOLAC) Furthermore, there are few data about pre-labor UR in scarred uteri. Objective: Since the key factor for management is timing, the aim of this study was to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…erefore, restoring gastrointestinal function is the focus of treatment for patients with scarred uterus undergoing secondary C-section. e study by scholars Vimercati et al showed that patients undergoing C-section and accepting carboprost methylate suppositories had significantly shorter bowel sound recovery time and anal exhaust more time than those in the control group (P < 0.001) and presented lower incidence rate of abdominal distension [23], which was similar to the results of this study. is demonstrates that carboprost methylate suppositories could directly act on the smooth muscles of intestinal tract and bladder and make them contract, thereby promoting the postoperative recovery of patients' gastrointestinal function and bladder function.…”
Section: Discussionsupporting
confidence: 90%
“…erefore, restoring gastrointestinal function is the focus of treatment for patients with scarred uterus undergoing secondary C-section. e study by scholars Vimercati et al showed that patients undergoing C-section and accepting carboprost methylate suppositories had significantly shorter bowel sound recovery time and anal exhaust more time than those in the control group (P < 0.001) and presented lower incidence rate of abdominal distension [23], which was similar to the results of this study. is demonstrates that carboprost methylate suppositories could directly act on the smooth muscles of intestinal tract and bladder and make them contract, thereby promoting the postoperative recovery of patients' gastrointestinal function and bladder function.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, the patient's late presentation finally resulted in a worse maternal and fetal outcome (intraoperative blood transfusion and hypoxic-ischemic fetal encephalopathy). According to our experience and other Authors' opinion, in order to improve the maternal-fetal outcome, high-risk patients (previous CS, abdominal pain, sickness, signs of peritoneal irritation and pelvic effusion) should be promptly identified and referred to adequate obstetric emergency units for urgent surgical treatment [10]. Moreover, Literature reports that in case of myomectomy, is more frequent the uterine rupture during pregnancy course and not during labor, compare to uterine rupture after cesarean section in which the uterine rupture is more frequent during labor [11].…”
Section: Discussionmentioning
confidence: 96%
“…Uterine rupture and previous placenta previa diagnosis having more time to manage safely the emergency (expert clinician, promptly available blood products, and well-equipped facilities) [10]. Therefore, the early screening of potentially at-risk pregnancies would allow to plan a periodic follow-up of these patients and the rapid detection of UR symptomatology.…”
Section: Compliance With Ethical Standardsmentioning
confidence: 99%
“…The literature has reported that readiness to diagnose and manage rare cases of UR could improve maternal-fetal outcome. Consequently, based on our experience and other authors’ opinions, high-risk patients should be promptly identified and, after counselling, referred to adequate obstetric emergency units for urgent surgical treatment [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since adenomyosis exhibits a diverse and heterogeneous disease spectrum, diagnostic imaging helps to manage patients properly [ 18 ]. Indeed, the international Morphological Uterus Sono-graphic Assessment (MUSA) group [ 21 , 22 , 23 , 24 , 25 ] published a consensus on the terminology to apply when describing myometrial lesions. By means of MUSA terminology, the sonographers could describe uterine adenomyosis with seven items that consist of: association of the presence of adenomyosis, discrimination of the location of the adenomyosis, distinction between the focal and diffuse disease, determination between a cystic and non-cystic lesion, examination of myometrial layer involvement, classification of the disease extent as mild, moderate, or severe, and measurement of the size of the lesion.…”
Section: Discussionmentioning
confidence: 99%